FORMULA OPTIMIZATION OF PLANTAGO (PLANTAGO MAJOR L.) HERB EXTRACT CHEWABLE TABLETS AT VARIOUS MANITOL- LACTOSE RATIO USING SIMPLEX LATTICE DESIGN - Septi Nur Hayati TN.; TN. Saifullah S.; Sri Mulyani (Pusbindiklat - LIPI, 2011)
The use of plantago (Plantago major L.) traditionally is less practical, therefore it needs to be developed into chewable tablet dosage form which is more acceptable. To prepare chewable tablet, lactose as a fi ller was used to substitute a part of mannitol which is relatively more expensive. Simplex lattice design (SLD) method was used to obtain the optimum ratio of mannitol-lactose mixture. Formula optimization using SLD was determined by testing of the granules physical properties: fl ow properties, compactibilities, and absorption capacities of water at various ratio. Plantago herbs were extracted by decoction and characterized. Granules of optimum formula were compressed into tablets and followed by testing its qualities: weight uniformities, hardness, brittleness, and qualitative analysis of chemical compounds using thin layer chromatography. Physical properties data of granules and chewable tablets were analysed using theoretical method and statistical with T test. The results showed that the increase of lactose proportion increased the fl ow properties, compactibilities, and absorption capacities of water. T-test at 95% confi dence level (α=0.05) indicated that SLD equalization was valid. Optimum area located between lactose-mannitol 100% : 0% and 20% : 80% with optimum formula was lactose-mannitol 100% : 0% as an optimum formula.